Engineering the Dimensional Interface of BiVO(4)-2D Reduced Graphene Oxide (RGO) Nanocomposite for Enhanced Visible Light Photocatalytic Performance - Sun, Jing (Nanomaterials (Basel), 2019)
Graphene as a two-dimensional (2D) nanoplatform is beneficial for assembling a 2D heterojunction photocatalytic system to promote electron transfer in semiconductor composites. Here a BiVO(4) nanosheets/reduced graphene oxide (RGO) based 2D-2D heterojunction photocatalytic system as well as 0D-2D BiVO(4) nanoparticles/RGO and 1D-2D BiVO(4) nanotubes/RGO nanocomposites are fabricated by a feasible solvothermal process. During the synthesis; the growth of BiVO(4) and the intimate interfacial contact between BiVO(4) and RGO occur simultaneously. Compared to 0D-2D and 1D-2D heterojunctions, the resulting 2D-2D BiVO(4) nanosheets/RGO composites yield superior chemical coupling; leading to exhibit higher photocatalytic activity toward the degradation of acetaminophen under visible light irradiation. Photoluminescence (PL) and photocurrent experiments revealed that the apparent electron transfer rate in 2D-2D BiVO(4) nanosheets/RGO composites is faster than that in 0D-2D BiVO(4) nanoparticles/RGO composites. The experimental findings presented here clearly demonstrate that the 2D-2D heterojunction interface can highlight the optoelectronic coupling between nanomaterials and promote the electron–hole separation. This study will motivate new developments in dimensionality factors on designing the heterojunction photocatalysts and promote their photodegradation photocatalytic application in environmental issues.